A Combined Value Focused Thinking-Soft Systems Methodology Approach to Structure Decision Support for Energy Performance Assessment of School Buildings - Bernardo, Hermano (2018)
Several technological, social and organizational factors influence energy management in school buildings, resulting in a complex situation away from the usual engineering approach. The selection of evaluation criteria to assess the energy performance of school buildings remains one of the most challenging aspects since these should accommodate the perspectives of the potential key stakeholders. This paper presents a comprehensive problem structuring approach combining Soft Systems Methodology and Value Focused Thinking to elicit and organize the multiple aspects that influence energy efficiency of school buildings. The main aim of this work is structuring the fundamental objectives to develop a criteria tree to be considered in a multi-criteria classification model to be used by management entities for rating overall energy performance of school buildings. This methodological framework helped grasping the main issues at stake for a thorough energy performance assessment of school buildings and the need to define adequate policies for improvement.